Effect of drying treatment on hydration ability of fresh waxy corn starch - Jiaqi Lin; Chaoyue Wei; Jina Han; Fuyu Yin; Yu Wei; Jiantao Song; Xiuying Xu; Yuzhu Wu; Jingsheng Liu (npj Science of Food)
Abstract The effects of microwave drying (MD), hot air drying (HD), and freeze vacuum drying (FD) on the hydration capacity of fresh waxy corn starch (FW) were investigated. The results revealed that FDFW exhibited the highest solubility and swelling power, peak viscosity, and stronger shear thinning behavior than MD and HD methods.It suggests that the internal structure of FDFW is relatively complete. FDFW possesses the highest enthalpy and the short-range ordered structure ratio. It demonstrated that the hydrogen bonds between the molecules or within the FW were preserved. The internal molecular chains of starch particles are arranged more systemically. Additionally, FDFW particles have a smooth surface and a complete and homogenous structure. This study can provide a theoretical basis for fresh corn products’ development and quality.